Metformin inhibits the migration and invasion of esophageal squamous cell carcinoma cells by downregulating the protein kinase B signaling pathway - He, Yindi (Oncol Lett, 2018)
Previous studies have suggested that metformin, a biguanide family member widely used as an oral antidiabetic drug, may inhibit proliferation and induce apoptosis in certain types of cancer cell. However, the molecular mechanisms underlying metformin-associated anticancer effects, and in particular antimetastatic effects, remain to be fully understood. The present study assessed the efficacy of metformin in inhibiting the migration and invasion of the esophageal carcinoma cell line EC109, and evaluated the effect of metformin on the protein kinase B (AKT) signaling pathway. EC109 cells were treated with 0, 5, 10 or 20 mM metformin during the logarithmic growth phase. A Transwell assay and western blot analysis revealed that metformin inhibited the migration and invasion of EC109 cells, nuclear factor-κB activation, matrix metallopeptidase 9 and N-cadherin expression in a phosphorylated-AKT dependent manner. These results suggested that metformin inhibits the migration and invasion of human esophageal carcinoma cells by suppressing AKT phosphorylation and regulating the expression of migration- and invasion-associated genes.